2023
DOI: 10.20525/ijrbs.v12i4.2444
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the role of entrepreneurship and SME in fostering South Africa's local economic development

Abstract: The purpose of the study was to investigate the roles of entrepreneurship and small and medium-sized businesses in fostering local economic development. Based on this assumption, this conceptual study attempts to investigate the function of small and medium-sized firms in LED. According to studies, the entrepreneurial spirit of the SME owner is a significant determinant of a SME's ability to surmount survival challenges and achieve sustainable growth. The article also attempts to locate and establish the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These constructs were used as the foundation for this study and as search criteria to uncover pertinent secondary sources that supported the findings, as will be explored in more detail below. A different body of research, however, asserts that SMMEs are at the vanguard of job creation and poverty reduction (Enaifoghe & Vezi-Magigaba, 2023;Real Economy Bulletin, 2017;Kongolo, 2010;Cant, Erdis & Sephapo 2014;Dzansi, 2004). According to Mitchell (2013:27), attention in South Africa is now concentrated on entrepreneurship to address this dilemma as a result of the failure of big industry and the state sector to produce jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These constructs were used as the foundation for this study and as search criteria to uncover pertinent secondary sources that supported the findings, as will be explored in more detail below. A different body of research, however, asserts that SMMEs are at the vanguard of job creation and poverty reduction (Enaifoghe & Vezi-Magigaba, 2023;Real Economy Bulletin, 2017;Kongolo, 2010;Cant, Erdis & Sephapo 2014;Dzansi, 2004). According to Mitchell (2013:27), attention in South Africa is now concentrated on entrepreneurship to address this dilemma as a result of the failure of big industry and the state sector to produce jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The goal of this study is to synthesize what is currently known about small and medium-sized businesses (SMEs) and their benefits to the digitalized economy and social society. It outlines the many traits of SMEs as well as the opportunities and difficulties they encounter in a globalized and digital economy (Enaifoghe & Vezi-Magigaba, 2022). Additionally, it points out areas that require additional research and where there are knowledge or data gaps.…”
Section: Introductionmentioning
confidence: 99%
“…The study also indicated that SMEs aim to improve policy synergies and address potential tradeoffs. Governments may help SMEs compete on an even playing field and improve their contributions to inclusive growth by developing and implementing an OECD strategy in the future (Enaifoghe & Vezi-Magigaba, 2022). This would happen in various economic and social circumstances.…”
Section: Introductionmentioning
confidence: 99%